Memory as politics and responsibilities deriving from the past (2019)
The article carries out a reflection on the politics of memory that should be developed in societies where massive human rights violations have occurred and whose processes are being guided by the normative principles of transitional justice. It starts out by analyzing the concepts of memory and history and the manner in which the Holocaust transformed their tasks in the 20th century. Then it goes on to examine two models of responsibility proposed by Iris Marion Young, and suggests how to use them in transitional justice. Finally, the article explains the tasks of the politics of memory in these contexts. © 2019 Universidad Nacional de Colombia. All rights reserved.